Seawater carbonate chemistry and intergenerational acclimation to environmental change in Acanthochromis polyacanthus - Sneha Suresh; Megan J Welch; Philip L Munday; Timothy Ravasi; Celia Schunter (PANGAEA, 2024)
Here using a multi-tissue approach we determine how variation in parental behavioural tolerance and exposure to elevated CO2 influences the developmental and intergenerational molecular responses of their offspring in the coral reef fish Acanthochromis polyacanthus to future ocean acidification (OA) conditions. This dataset is included in the OA-ICC data compilation maintained in the framework of the IAEA Ocean Acidification International Coordination Centre (see https://oa-icc.ipsl.fr). Original data were downloaded from the PANGAEA dataset (see Source). In order to allow full comparability with other ocean acidification data sets, the R package seacarb (Gattuso et al, 2024) was used to compute a complete and consistent set of carbonate system variables, as described by Nisumaa et al. (2010). In this dataset the original values were archived in addition with the recalculated parameters (see related PI). The date of carbonate chemistry calculation by seacarb is 2024-12-03.